Assessing farmer's exposure to pesticides and the risk for non-communicable diseases: A biomonitoring study - Kumar, Dileshwar; Sinha, Sukesh Narayan; Rajendra, Sangaraju; Sharma, Kanika (The Science of the total environment, 2023)
This cross-sectional study aimed to assess the adverse effects of pesticide use in humans, such as non-communicable diseases, using acetylcholinesterase (AChE) and pesticide concentrations in blood samples. A total of 353 samples (290 case and 63 control) were collected from participants with >20 years of experience in agricultural pesticide use. The pesticide and AChE concentrations were determined using Liquid Chromatography with tandem mass spectrometry (LC-MS/MS) and Reverse Phase High Performance Liquid Chromatography (RP-HPLC). Various health risks from pesticide exposure were assessed, including dizziness or headache, tension, anxiety, confusion, loss of appetite, loss of balance, concentration difficulties, irritability, anger, and depression. These risks may be influenced by the duration and intensity of exposure, the type of pesticide, and environmental factors in the affected areas. A total of 26 pesticides were detected in the blood samples from the exposed population, including 16 insecticides, three fungicides, and seven herbicides. Pesticide concentrations ranged from 0.20 to 12.12 ng/mL, and were statistically significant between the case and control groups (p < 0.05, p < 0.01, and p < 0.001). A correlation analysis was performed to determine statistically significance between pesticide concentration and symptoms of non-communicable diseases, such as Alzheimer's, Parkinson's, obesity, and diabetes. The estimated AChE levels in case and control blood samples were 21.58 ± 2.31 and 24.13 ± 1.08 U/mL, respectively (mean ± SD). The AChE levels were significantly lower in case samples than in controls (p < 0.001), which is considered to be an effect of long-term pesticide exposure, and is the cause of Alzheimer's disease (p < 0.001), Parkinson's disease (p < 0.001), and obesity (p < 0.01). Chronic exposure to pesticides and low levels of AChE are somewhat related to non-communicable diseases. [Display omitted] •Cross-sectional study of 353 subjects was assessed.•Acetylcholinesterase enzyme was used as bio-marker of non-communicable diseases.•Pesticide exposure and chronic risk factor in the agricultural population•Lower level of acetylcholinesterase linked with some of the non-communicable disease (obesity, Alzheimer's, and Parkinson's).